Education programmes on performance-based assessment for allied health and nursing clinical educators: A scoping review protocol [version 3; peer review: 1 approved, 2 approved with reservations] - Lucy Alpine; Emer Barrett; David Mockler; Anne O'Connor; Julie Broderick (HRB Open Research)
Background Performance-based assessment (PBA) is a complex process undertaken in the workplace by healthcare practitioners known as clinical educators, who assist universities in determining health professional students’ readiness for independent practice. Preparing healthcare professionals for PBA is considered essential to ensuring the quality of the assessment process in the clinical learning environment. A preliminary search of the literature indicated a paucity of research guiding the development of education programmes that support practice educators to understand and implement PBA. Objective The aim of this scoping review is to investigate and describe education programmes delivered to allied health and nursing clinical educators, to develop PBA knowledge and skills. Methods This review will follow the Joanna Briggs Institute (JBI) methodology for conducting scoping reviews. Electronic databases relevant to this research topic will be searched including, EMBASE, ERIC, MEDLINE (Ovid), Web of Science and CINAHL and other targeted databases for grey literature. Studies that include PBA as the main focus or a component of the education programmes, of any format, delivered to clinical educators in allied health and nursing will be included. Studies may report the design and/or implementation and/or evaluation of PBA education programmes. Relevant English language publications will be sought from January 2000 to October 2022. Two reviewers will screen all titles and abstracts against the inclusion/exclusion criteria, and publications deemed relevant will be eligible for full text screening, confirming appropriateness for inclusion in the scoping review. Data will be charted to create a table of the results, supported a by narrative summary of the findings in line with the review objectives.